2021
DOI: 10.1126/sciimmunol.abg6461
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 mutations in MHC-I-restricted epitopes evade CD8 + T cell responses

Abstract: CD8+ T cell immunity to SARS-CoV-2 has been implicated in COVID-19 severity and virus control. Here, we identified nonsynonymous mutations in MHC-I-restricted CD8+ T cell epitopes after deep sequencing of 747 SARS-CoV-2 virus isolates. Mutant peptides exhibited diminished or abrogated MHC-I binding in a cell-free in vitro assay. Reduced MHC-I binding of mutant peptides was associated with decreased proliferation, IFN-γ production and cytotoxic activity of CD8+ T cells isolated from HLA-matched COVID-19 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
169
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(192 citation statements)
references
References 70 publications
(89 reference statements)
9
169
0
Order By: Relevance
“…Moreover, our global analysis validated the presence of two previously reported CD8+ T cell mutated epitopes (i.e. GLMWLSYFI à GFMWLSYFI, found in 38 genomes; and MEVTPSGTWL à MKVTPSGTWL, found in 23 genomes), which were shown to lose binding to HLA-A*02:01 and -B*40:01, respectively, in addition to disrupt epitope-specific CD8+ T cell response in COVID-19 patients (Figure S3) (Agerer et al, 2021). Together, these results demonstrate that mutations driving the global genomic diversity of SARS-CoV-2 can drastically disrupt HLA binding of clinically relevant CD8+ T cell epitopes, including epitopes encoded by the immunodominant S and N antigens, therefore affecting epitope-specific T cell responses in COVID-19 patients.…”
Section: The Global Diversity Of Sars-cov-2 Genomes Influences the Repertoire Of T Cell Targetssupporting
confidence: 82%
“…Moreover, our global analysis validated the presence of two previously reported CD8+ T cell mutated epitopes (i.e. GLMWLSYFI à GFMWLSYFI, found in 38 genomes; and MEVTPSGTWL à MKVTPSGTWL, found in 23 genomes), which were shown to lose binding to HLA-A*02:01 and -B*40:01, respectively, in addition to disrupt epitope-specific CD8+ T cell response in COVID-19 patients (Figure S3) (Agerer et al, 2021). Together, these results demonstrate that mutations driving the global genomic diversity of SARS-CoV-2 can drastically disrupt HLA binding of clinically relevant CD8+ T cell epitopes, including epitopes encoded by the immunodominant S and N antigens, therefore affecting epitope-specific T cell responses in COVID-19 patients.…”
Section: The Global Diversity Of Sars-cov-2 Genomes Influences the Repertoire Of T Cell Targetssupporting
confidence: 82%
“…In addition, it remains to be elucidated whether pre-existing memory T cells that are cross-reactive to SARS-CoV-2 play a protective or detrimental role in patients with COVID-19. SARS-CoV-2 mutations that abrogate binding to MHC have been reported (Agerer et al, 2021), a recent study reported insignificant impacts of variants on SARS-CoV-2-specific CD4 + and CD8 + T-cell responses (Tarke et al, 2021). Most T-cell epitopes were conserved among emerging SARS-CoV-2 variants.…”
Section: T-cell Responses Elicited By Covid-19 Vaccinesmentioning
confidence: 96%
“…To experimentally assess the impact of the identified nonsynonymous mutations on peptide binding to MHCI, we performed differential scanning fluorimetry (DSF) ( 38 , 40 ). Briefly, we performed UV-mediated peptide-exchange reactions with H2-D b -UVCP (ultraviolet light-cleavable peptide) complexes in the presence of WT or the mutant peptides.…”
Section: Resultsmentioning
confidence: 99%
“…The UV-cleavable peptides for H2-D b and H2-K b , ASNENJETM ( 36 ) and FAPGNYJAL ( 39 ) respectively, were purchased crude (70% purity) from Intavis Peptide Services and were used in all differential scanning fluorimetry experiments. The peptide-MHCI complexes for the differential scanning fluorimetry experiments were made ( 37 ) and the experiments performed as described previously ( 40 ). The GP33-41 peptides used in Figures 3D, E were the same as for the intracellular cytokine experiment (see above).…”
Section: Methodsmentioning
confidence: 99%